Pemahaman Peserta Didik saat Pembelajaran Daring Selama Pandemi Covid-19 - Eka Ariyanti; Hariyanto Hariyanto; Widia Darma (SAP (Susunan Artikel Pendidikan), 2022)
The Covid-19 pandemic changed the learning of Buddhist Education, which was initially carried out by face-to-face then changed into online learning. Learners' understanding is influenced by how teachers convey learning and conditions during the online learning process. This study aims to: (1) find out how much the influence of online learning during the Covid-19 pandemic has on learners' level of understanding. (2) to explain the influence of online learning during the Covid-19 pandemic on students' level of understanding of Buddhist education subjects. This research is a quantitative study with a type of correlational approach conducted at Semarang Regency Junior High School in AprilJune 2021. The population in this study was 125 learners, while the sample used was 60 learners— sampling using simple random sampling techniques. Data collection techniques and instruments were carried out using questionnaires. Data analysis techniques used simple linear regression analysis with the help of the SPSS 16 program. Based on the research and data analysis results, online learning during the Covid-19 pandemic has influenced students' level of understanding by 0.641. When viewed from the value of R square is 29%. The influence of online learning on learners' level of understanding is positive and significant, with a simple linear regression test showing that the correlation coefficient of 0.540 is positive.